Mataura flood 2020, Aotearoa New Zealand: A case study highlighting resilience through community spirit. (November 2022) - Blake, Denise; Hodgetts, Darrin; Thompson, Jessica; Johnston, David
Abstract: Mataura is a small township in the Southland region of Te Waipounamu (South Island, Aotearoa New Zealand), which displayed the importance of community spirit as people were evacuated during the Mataura River flood of February 2020. The article draws on the case of Mataura during this event, as conveyed through the vlogs of the person working as the Mataura Community Development Coordinator at that time. The vlogs were analysed through a narrative lens to develop an understanding of how community processes can serve to improve responses and recovery from such disasters. Leveraging insights from previous research, we identify salient issues for communities, including access to practical resources, mental and emotional wellbeing, and the importance of effective communication during evacuations. Presented as a single case study, this article offers a worked exemplar from frontline insights into the mechanisms and functions of a community during times of adversity.